Scientific contributions of Ibn Hazm - Shuriye, Abdi Omar; Femi Salami , Abdulazeez (InderScience Publisher, 2011)
The objective of this research is to explore the contributions of Ibn Hazm in science and technology. The research also explains the religious situation, sociopolitical situation, and scientific development during this period. The methodology used is analytical and historical in nature. The significant of the research lies in the fact that it revisits the heritage of Islamic and Arabic contributions to science and technology.